2023
DOI: 10.1371/journal.pbio.3002009
|View full text |Cite
|
Sign up to set email alerts
|

Illusory object recognition is either perceptual or cognitive in origin depending on decision confidence

Abstract: We occasionally misinterpret ambiguous sensory input or report a stimulus when none is presented. It is unknown whether such errors have a sensory origin and reflect true perceptual illusions, or whether they have a more cognitive origin (e.g., are due to guessing), or both. When participants performed an error-prone and challenging face/house discrimination task, multivariate electroencephalography (EEG) analyses revealed that during decision errors (mistaking a face for a house), sensory stages of visual inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 100 publications
2
3
0
Order By: Relevance
“…2 G ). In line with previous work ( Alilović et al, 2023 ), decoding AUC was significantly below chance level for incorrect decisions (one-sample, two-sided t test against 0.50: t (26) = −4.34; p < 0.001; d = 0.83; BF 01 = 6.83 × 10 −3 ), suggesting that neural activity of incorrect trials contained “illusory” stimulus orientation information, i.e., information about the nonpresented stimulus orientation that was reported. Neither ATX nor DNP modulated overall decoding accuracy (ATX: F (1,26) = 0.01, p = 0.92, η p 2 = 0.00, BF 01 = 4.91; DNP: F (1,26) = 0.02, p = 0.88, η p 2 = 0.00, BF 01 = 4.94).…”
Section: Resultssupporting
confidence: 92%
“…2 G ). In line with previous work ( Alilović et al, 2023 ), decoding AUC was significantly below chance level for incorrect decisions (one-sample, two-sided t test against 0.50: t (26) = −4.34; p < 0.001; d = 0.83; BF 01 = 6.83 × 10 −3 ), suggesting that neural activity of incorrect trials contained “illusory” stimulus orientation information, i.e., information about the nonpresented stimulus orientation that was reported. Neither ATX nor DNP modulated overall decoding accuracy (ATX: F (1,26) = 0.01, p = 0.92, η p 2 = 0.00, BF 01 = 4.91; DNP: F (1,26) = 0.02, p = 0.88, η p 2 = 0.00, BF 01 = 4.94).…”
Section: Resultssupporting
confidence: 92%
“…We presented evidence of two crucial stages in the processing of visual information during perceptual decision making in mice, replicating and extending previous work in both humans and animals (Alilović et al, 2023;Allen et al, 2017;Dehaene and Changeux, 2011;Del Cul et al, 2007;Oude Lohuis et al, 2022b;Steinmetz et al, 2019;van Vugt et al, 2018). Neural recordings collected from two independent labs using two different tasks revealed that V1 firing rate at 100 ms after stimulus change was uniquely modulated by the saliency of the stimulus and not by the decision made by the mouse (Oude Lohuis et al, 2022b) (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…For these reasons, we decided to develop a minimal model of neural dynamics (Chaudhuri et al, 2015; Joglekar et al, 2018), which allowed us to test the contribution of individual feedback pathways to generating and propagating report-related activity across the cortical network. Compared to previous studies following a similar approach for studying report-related activity in the human brain (Alilović et al, 2023; Castro et al, 2020; Dehaene et al, 2003; Dehaene and Changeux, 2005), we leveraged the recently established availability of functional and structural data in mice (Harris et al, 2019; Knox et al, 2019; Oude Lohuis et al, 2022b; Steinmetz et al, 2019) to develop a computational model with anatomically faithful connectivity strengths between cortical regions and capable of reproducing patterns of spiking activity observed in mice performing perceptual tasks. We developed a model network composed of mouse primary visual cortex (V1), posterior parietal cortex (PPC) and prefrontal cortex (PFC).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, others have argued that already local recurrent interactions reflect subjective phenomenal experience (Block, 2005; Lamme, 2010). Moreover, markers like the P300 and ours for global recurrent processing may reflect functions not directly related to conscious experience, like report or decision-making (Alilović et al, 2023; Canales-Johnson et al, 2023; Pitts et al, 2018). Another way forward therefore consists in combining no-report paradigms (Sergent et al, 2021; Tsuchiya et al, 2015) with our EEG markers to examine whether local or global recurrent processing more accurately reflects consciousness in the absence of report.…”
Section: Discussionmentioning
confidence: 99%